Pengujian Turbin Air Pusaran Gravitasi dengan Variasi Overlap Ratio Rotor - Muhammad Luthfi; Meri Rahmi; Rachmatullah - (Department of Mechanical Engineering, Universitas Andalas, 2022)
The gravitational water vortex turbine is a turbine system that can convert the energy from artificial water vortex by means of the drained water through the basin outlet to the kinetic energy of rotor rotation. This type of turbine system is able to produce energy despite the low head of water flow. Many researches were conducted to improve the efficiency of this turbine by changing the shape of basin, or the rotor. Meanwhile, the Savonius rotor has good starting rotation and ease of fabrication, but low efficiency. One way to increase the efficiency of this rotor is to apply the gap between the blades which is called Overlap Ratio (OR). In this research, the gravitational water vortex turbine with the conical-shape basin was combined with the various-OR Savonius rotors with area proportion of 26,88% and without endplate and the effect was observed to the efficiency of turbine. The volume flowrate of channel was maintained constant at 0,005 m3/s while mass was added gradually for the torque measurement system by using rope brake dynamometer. The result showed that for all rotors, the greater efficiency occurred in the low rotational speed. Moreover, the rotor with OR of 0,15 had greater mechanical efficiency which was around 22,78% for the rotor with endplate 26,88% and 27,18% for the rotor without endplate than rotor with OR of 0. Meanwhile, rotor without endplate had higher maximum mechanical efficiency for all OR variation than that with endplate 26,88%.